Harry potter and the philosopher's stone - Rowling, J.K (London : Bloomsbury Pub, 1997)
Harry Potter thinks he is an ordinary boy until he is rescued by an owl, taken to Hogwarts School of Witchcraft and Wizardry, learns to play Quidditch and does battle in a deadly duel. The reason: Harry Potter is a wizard
Harry Potter thinks he is an ordinary boy until he is rescued by an owl, taken to Hogwarts School of Witchcraft and Wizardry, learns to play Quidditch and does battle in a deadly duel. The reason: Harry Potter is a wizard! It is a story full of surprises and jokes. Rowling uses classic narrative devices with flair and originality and delivers a complex and demanding plot in the form of a hugely entertaining thriller
This book is about harry potter rolling stone .a story for childerns
Keywords: Brujas Cuentos infantiles; Children's stories; England Fiction